2010
DOI: 10.3233/prm-2010-0129
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of supported standing programs

Abstract: Objective: The routine clinical use of supported standing in hospitals, schools and homes currently exists. Questions arise as to the nature of the evidence used to justify this practice. This systematic review investigated the available evidence underlying supported standing use based on the Center for Evidence-Based Medicine (CEBM) Levels of Evidence framework. Design: The database search included MEDLINE, CINAHL, GoogleScholar, HighWire Press, PEDro, Cochrane Library databases, and APTAs Hooked on Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…As part of a 2010 systematic review, Glickman et al 11 concluded that supported standing clinical investigations should seek to include functional, behavioral, and cognitive outcomes, alongside physiological measures. Therefore, future studies of supported standing in boys with DMD should include outcomes across all 3 components of the International Classification of Functioning, Disability and Health model, particularly those that reflect activity and participation components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a 2010 systematic review, Glickman et al 11 concluded that supported standing clinical investigations should seek to include functional, behavioral, and cognitive outcomes, alongside physiological measures. Therefore, future studies of supported standing in boys with DMD should include outcomes across all 3 components of the International Classification of Functioning, Disability and Health model, particularly those that reflect activity and participation components.…”
Section: Discussionmentioning
confidence: 99%
“…Supported standing has also been recommended, both historically 10 and as part of published clinical care guidelines for DMD. 9 Supported standing programs have been shown to improve lower extremity range of motion and BMD in children with cerebral palsy 11,12 and have also been recommended for children with neuromuscular diseases on the basis of expert opinion. 13,14 Despite potential benefits and common clinical use, no empirical studies evaluating standing in boys with DMD have been reported and no evidence-based clinical recommendations currently exist.…”
Section: Introduction and Purposementioning
confidence: 99%
“…The intervention does not provide a direct prompt to trigger the behaviour at any point in time. (Glickman, Geigle, & Paleg, 2010;Paleg, Smith, & Glickman, 2013;Verschuren, Peterson, Balemans, & Hurvitz, 2016), the more general literature concerning health behaviours is also included. Health behaviour is described by the World Health Organisation as "any activity undertaken by an individual, regardless of actual or perceived health status, for the purpose of promoting, protecting or maintaining health" (Nutbeam 1998, p.355).…”
Section: B=matmentioning
confidence: 99%
“…It improves preserved muscle strength, range of motion and reduces the risk of contractures and spasticity in lower limbs. Standing can also promote vital organ capacity including pulmonary, bowel and bladder function, bone health, circulation which may in turn minimize the occurrence of pressure ulcers (Alekna et al, 2008;Damcott, Blochlinger, & Fouolds, 2013;Glickman, Geigle, & Paleg, 2010;Hohman, 2011;Paleg, Smith, & Glickman, 2013;Robling et al, 2002;Speigle, Maureer, & Sorenblum, 2010). Other than physical aspects, routine standing can provide numerous psychosocial and quality of life benefits (Arva et al, 2009;Dicianno, Morgan, Lieberman, & Rosen, 2013).…”
Section: Introductionmentioning
confidence: 99%